Effect of Place and Time Storage on the Quality of Tubers Amorphophallus muelleri Blume - Al Adawiah, Putri Rabiah; Azrianingsih, Rodiyati; Mastuti, Retno (Graduate School, Universitas Brawijaya, 2019)
Porang tubers are plant commodities that physiologically susceptible to damage. Longtime storage can decrease the quality of tubers. Furthermore, the presence of fungi or bacteria makes tubers cannot be stored in a long time. Decreasing quality of Porang tuber became a problem because of the higher demand for porang tubers. This research was conducted to determine the suitable place and time storage of porang tubers. Therefore, farmers can control or reduce the decrease in tuber quality. Methods of this research were an observation of color change based on the Munsell Color System, odor observation, hardness observation using penetrometer, the rotten area of tuber was measured using Leaf Area Meter, shrinkage of tuber weight, the percentage of rotten and sprouted tubers, density, and moisture content by the oven method. The results of this study were analysed statistically by ANOVA test. The hardness of the tubers has a significant effect on the storage place (soil, rack, and floor) for period 14 weeks. Storage time has an effect on changes of the weight loss, moisture content and decay area. The longer the tuber stored the higher percentage of sprouted and rotten tubers. The color of porang tubers change and the odor in the part of the rotten tubers increase during the storage period in each storage place. Porang tubers should not be stored for more than two weeks and placed on a rack to minimize the damage of the tubers.Keywords: Physical change, porang tubers, storage time.